The Effectiveness of Zoom Meeting Application During The Distance Learning: A Review - Tuhu Setyono; Agrissto Bintang Aji Pradana (Prosiding University Research Colloquium, 2022)
Covid-19 has impeded all current operations, particularly in the sector of education. Distance learning is one of the initiatives to limit the virus's rapid spread. Learning needs media that is made available by pandemic circumstances, such as the Zoom meeting application. This program is based on contemporary educational demands, and numerous capabilities are accessible to aid in communication through voice and graphics. Additionally, the usage of zoom meetings, particularly at the primary school level, is one step in incorporating technology into learning. The purpose of this study is to determine the effectiveness of using Zoom meeting in virtual classrooms through performing a literature review , scanning a database of diverse publications on Google Scholar. 15 of the 256 articles which were considered as relevant. The findings suggest that the usage of the Zoom Meeting application in distance learning was beneficial.